Transient Cortical Blindness after Digital Subtraction Angiography of Cerebral Vessels - Parajuli, Shreeya; Rajbhandari, Pravesh; Acharya, Sameer; Pant, Basant (Nepal Journal of Neuroscience, 2017)
Transient blindness following cerebral angiography is a rare but known entity. We report a case of transient cortical blindness after cerebral angiography. The patient presented with is chemic stroke and the angiography was performed to rule out carotid artery stenosis. The patient, however, gradually regained his vision over a period of 3 days. This article is to understand one of the most unusual complications that may occur while performing angiography Nepal Journal of Neuroscience, Vol. 14, No. 2,  2017 Page: 36-38